Co-operative harmless treatment and neutralization utilization process research of LPG spent caustic coupled chloroaluminate ionic liquid spent catalysts. (April 2023) - Zhang, Xuemian; Liu, Tao; Zhang, Yimin; Cai, Zhenlei; Wan, Qian
Abstract: In the petrochemical industry, due to strong acids and toxic heavy metals, chloroaluminate ionic liquid spent catalysts pose a potential environmental risk. Given the strong alkalinity and high pollution load, the treatment step for liquefied petroleum gas (LPG) spent caustic requires adding acid, resulting in significant acid consumption and the risk of secondary pollution. According to the characteristics of these two types of solid waste, the coupling process of LPG spent caustic and chloraluminate ionic liquid waste catalyst is proposed with the goal of resource and harmlessness. The LPG spent caustic and the chloroaluminate ionic liquid spent catalyst are pretreated by precipitation-flocculation and hydrolysis, respectively, after which they are neutralized. The main factors in the pretreatment and neutralization process are systematically examined. Under optimum circumstances, 98 % of the sulfide from LPG spent caustic was removed, 86.8 % of the chemical oxygen requirement was removed, and the oil content in the treated solution was 10 mg/L. The hydrolysis reaction was milder when the hydrolysis media was mixed with the chloroaluminate ionic liquid spent catalyst at a volume ratio of 40:1. By changing the hydrolysis medium, it was confirmed that the neutralizing solution containing sodium chloride had an inhibitory effect on the reaction when reused in the hydrolysis reaction of the spent catalyst. The treated LPG SC and the acidic hydrolysate were neutralized at a volume ratio of 14.8:100.The pH after the reaction was 7, and the recoveries of aluminum and copper ions were 99.99 % and 93.36 %, respectively. The precipitates were calcined at high temperatures, and the characterization of the calcined products confirmed the formation of copper aluminate spinel by XRD, FT-IR, and SEM-EDS. The COD, sulfide, and oil indicators in the neutralization solution meet the tertiary effluent discharge standards of China's National Comprehensive Effluent Discharge Standard (GB 8978-1996). The process eliminates the risk of high sulfide and COD from the LPG SC and recovers the spent catalyst's metal resources. In addition, the whole process has no additional added acid or alkali. A new approach to disposing of these two hazardous wastes (LPG SC and chloroaluminate ionic liquid spent catalysts) for the petrochemical industry is offered. Graphical abstract: Unlabelled Image Highlights: Achieving coupled utilization and treatment of petrochemical hazardous waste Coupling process without addition of exogenous acids and bases The recovery rates for copper and aluminum were 99.9 % and 93.3 %, respectively. Sulfide and COD removal in LPG SC was 99.97 % and 98.27 %, respectively.